Nephrite of Bazhenovskoye Chrysotile–Asbestos Deposit, Middle Urals: Localization, Mineral Composition and Color - Evgeniy V. Kislov (MDPI AG, 2021)
In the Bazhenovskoye chrysotile–asbestos deposit (Middle Urals), nephrite bodies of the serpentinite type were found on the contact of after gabbro rodingites and serpentinites. The color is uniform to non-uniform, green to light green, bluish green, greyish green, and whitish. Spots, streaks, lenticules of bright bluish-green or, on the contrary, light green color are sometimes noted. The nephrite is mostly comprised of tremolite. Chromite decreases the quality of the ornamental stone, but it is replaced by chrome grossular, which gives the nephrite a brighter bluish-green color locally. Crushed grains of chromite contain increased concentrations of Zn and Mn. The quality of the nephrite is decreased by serpentine and talc, as well as by fractures due to drilling and blasting works. The specific feature of the nephrite in the Bazhenovskoye deposit is the formation of nickeline, maucherite, and uvarovite. The green color is associated with Fe2+ ions. The nephrite of the Bazhenovskoye deposit meets the requirements for an ornamental stone. The origin of this nephrite includes a combination of metasomatic and metamorphic processes.